2011
DOI: 10.1371/journal.pone.0028223
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Analysis on DNA Methylation and the Expression of Both mRNA and microRNA in Bladder Cancer

Abstract: BackgroundDNA methylation aberration and microRNA (miRNA) deregulation have been observed in many types of cancers. A systematic study of methylome and transcriptome in bladder urothelial carcinoma has never been reported.Methodology/Principal FindingsThe DNA methylation was profiled by modified methylation-specific digital karyotyping (MMSDK) and the expression of mRNAs and miRNAs was analyzed by digital gene expression (DGE) sequencing in tumors and matched normal adjacent tissues obtained from 9 bladder uro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 78 publications
3
37
1
Order By: Relevance
“…The other genes are mostly tumor suppressor genes that should have a low degree of promoter methylation (0–10%) in normal urothelium [48]–[54]. Methylation levels of 10–15% for C1QTNF6 in UROtsa were reported before, being in good agreement with our value of 12% in UROtsa-4 [29].…”
Section: Discussionsupporting
confidence: 90%
“…The other genes are mostly tumor suppressor genes that should have a low degree of promoter methylation (0–10%) in normal urothelium [48]–[54]. Methylation levels of 10–15% for C1QTNF6 in UROtsa were reported before, being in good agreement with our value of 12% in UROtsa-4 [29].…”
Section: Discussionsupporting
confidence: 90%
“…Epigenetic silencing of miRs via hypermethylation of CpG shore regions has been documented in BC [7], though some have reported that the genome-wide methylation patterns between BC and normal adjacent tissue are similar [46]. Saito showed that tumor suppressor miR-126, which was down-regulated in cell lines and BC, could be up-regulated in cell lines by DNA methylation and histone deacetylation inhibitors [47].…”
Section: Resultsmentioning
confidence: 99%
“…[126][127][128][129][130] Although the mechanisms underlying miRNA dysregulation in human bladder cancer are not fully determined, proof-of-principle experiments have established a tight link between epigenetic changes, such as aberrant DNA methylation and histone modifications, and altered miRNA expression in bladder carcinogenesis. [131][132][133] For instance, Saito et al 134 have shown that simultaneous treatment of T24 human bladder cancer cells with 5-aza-2'-deoxycytidine (5-Aza-CdR) and 4-phenylbutyric acid, which inhibit DNA methylation and histone deacetylase, respectively, resulted in upregulation (>3-fold) of 17 out of 313 (5.4%) human miRNAs examined. Epigenomic studies in various types of human cancer, including bladder cancer, have shown that the number of dysregulated miRNA genes with aberrant DNA methylation at their promoter CpG islands and/ or the flanking CpG "shores" (regions with less CpG density) is rapidly rising.…”
Section: Concluding Remarks: Potential Challenges and Future Directionsmentioning
confidence: 99%